Advances in lung cancer surgery - Hennon, Mark W. (Medknow Publications & Media Pvt Ltd, 2012)
The last few years have witnessed an explosion of the use of minimally invasive techniques for the detection, diagnosis, and treatment of all stages of lung Cancer. The use of these techniques has improved the risk-benefit ratio of surgery and has made it more acceptable to patients considering lung surgery. They have also facilitated the delivery of multi-modality therapy to patients with advanced lung cancer. This review article summarizes current surgical techniques that represent the “cutting edge” of thoracic surgery for lung cancer.